Generalization of Retractable and Coretractable Modules - Zeyada, Nasr; Al-Mallah, O.; Al-Zmammy, A. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this work, we extend the notion of retractability to s- retractability. An R-module is called s-retractable if for all nonzero . Also we extend coretractable modules to semi-coretractable modules. An R-module is called semi-coretractable if for all maximal essential submodule of . We investigate theseclasses of modules and extend some of main theorems on retractable and coretractable modules to s-retractable and semi-coretractable modules, respectively.